Toxicidade aguda do sulfato de cobre e do triclorfon para três espécies de daphnias em presença e ausência de sedimento - Romero Arauco, Luis Ricardo [UNESP] (2002)
The aim of this study was to determine the acute toxicity, LE50-48h, of copper sulfate and of trichlorfon, to compare sensitivities and to evaluate the risk of environmental poisoning for three species of daphnias (Daphnia similis, Daphnia magna and Daphnia laevis), in the presence and absence of sediment. The tests for acute toxicity were performed under laboratory conditions, in a climatized room according to standardized methods with some adaptations. The LE50-48h values of copper sulfate calculated for D. magna were 0.345 mg/L with sediment and 0.045 mg/L without sediment; for D. similis, 0.282 mg/L with sediment and 0.042 mg/L without sediment; and for D. laevis 0.140 mg/L with sediment and 0.107 mg/L without sediment. The LE50-48h values of trichlorfon calculated for D. magna were 299.70 ng/L with sediment and 0.70 without sediment; for D. similis, 381.62 with sediment and 0.52 ng/L without sediment; and for D. laevis, 282.72 ng/L with sediment and 0.92 ng/L without sediment. Trichlorfon was more toxic than copper sulfate for the three species of daphnias. Sediment diminished the toxicity of both trichlorfon and copper sulfate for the three species of daphnias. In the absence of sediment, D. magna and D. similis did not show any difference in sensitivity to the two agrochemicals. However, D. laevis was significantly more sensitive than the other two species. In the presence of sediment, there was a difference in sensitivity among the species of daphnias, with D. magna being the most sensitive, followed by D. similis and D. laevis, showing less sensitivity to copper sulfate. In the absence of sediment, the three species of daphnias did not show any difference in sensitivity to trichlorfon. In the presence of sediment, D. magna and D. laevis showed no difference in sensitivity to trichlorfon. The use of copper sulfate and trichlorfon in pisciculture was classified as being of high risk ...